Endoscopic and Surgical Gastrostomy and Jejunostomy Tube Placement - Bauman, Marita D.; El-Hayek, Kevin (Digestive Disease Interventions, 2018)
Enteral access is a common request for consulting surgeons and interventionists. Prior to the 1980s, such a consultation often necessitated open surgical intervention whereas today, enteral access is often performed via several minimally invasive methods. Tools and techniques for minimally invasive enteral access have changed drastically due to advancements in the fields of endoscopy, laparoscopy, and interventional radiology. Percutaneous endoscopic gastrostomy tube placement is one such advancement. Since its first development, its basic principles have been applied to other minimally invasive techniques, which have resulted in an expansion of techniques for establishment of enteral access. In this article, we outline various endoscopic and surgical techniques for gastric and jejunal access.
Keywords: percutaneous endoscopic gastrostomy; PEG tube; jejunostomy; gastrostomy; PEG with jejunal extension; PEG-JET; T-fasteners; direct percutaneous endoscopic jejunostomy